1985
DOI: 10.1002/cne.902380106
|View full text |Cite
|
Sign up to set email alerts
|

Inferior colliculus of the house mouse. I. A quantitative study of tonotopic organization, frequency representation, and tone‐threshold distribution

Abstract: Electrophysiological mapping was used to study frequency representation in the inferior colliculus (IC) of the mouse. In the lateral nucleus (LN) only part of the frequency range of hearing was represented and tonotopicity was separate from that in the rest of the IC. Highest frequencies occupied the medial part (M) of the central nucleus (CN). A single complete representation of the hearing range was present only if representations in the dorsal cortex (plus dorsomedial nucleus) and CN (including M) were comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
136
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(160 citation statements)
references
References 32 publications
23
136
1
Order By: Relevance
“…However, some caution may be warranted with respect to the boundaries established in this manner because their correlation with functional borders established in vivo is tentative (2,22,23). In addition, recorded neurons were localized based on a combination of the gross anatomical features, cell morphology, and intrinsic physiology.…”
Section: Discussionmentioning
confidence: 99%
“…However, some caution may be warranted with respect to the boundaries established in this manner because their correlation with functional borders established in vivo is tentative (2,22,23). In addition, recorded neurons were localized based on a combination of the gross anatomical features, cell morphology, and intrinsic physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the ICC should provide access to neural circuits essential for hearing restoration by an auditory prosthesis. The ICC has a highly organized tonotopic structure (Geniec and Morest 1971;Malmierca et al 1995;Merzenich and Reid 1974;Rose et al 1963;Schreiner and Langner 1997;Serviere et al 1984;Stiebler and Ehret 1985), which should allow for systematic access to different frequency regions using a penetrating electrode array auditory midbrain implant (AMI). In fact, the AMI should be able to access low-frequency regions (Ͻ1 kHz) in the ICC, which is usually not achievable in the cochlea with current CIs.…”
Section: Introductionmentioning
confidence: 99%
“…In normal hearing mice, there exists a topographic frequency map that originates at the inner ear and is preserved in all major auditory nuclei (Ehret and Romand, 1997;Muller et al, 2005). In the mouse IC, this tonotopic map normally represents lower frequencies dorsolaterally and progressively higher frequencies ventromedially (Stiebler and Ehret, 1985). Willott (1984) observed that the tonotopic map in IC is severely disrupted in mice suffering from sensorineural hearing loss.…”
Section: Excitatory Frequency Response Areasmentioning
confidence: 99%
“…Neurons in the ventral IC normally respond to high frequencies, but as sensorineural hearing loss progresses, their sensitivity shifts to lower frequencies (Stiebler and Ehret, 1985;Willott, 1984). Several mechanisms have been proposed that may underlie changes in tonotopic organization in mice with sensorineural hearing loss (Willott, 1984;Willott, 1986).. One explanation for altered tonotopy involves a change in sensitivity in the cochlea (Willott, 1984).…”
Section: Multiply Tuned Neurons and Altered Tonotopymentioning
confidence: 99%
See 1 more Smart Citation